(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
The collapsible crab trap commonly used to harvest blue swimming crab (Portunus pelagicus) in Banten Bay employs a 1.0-inch mesh wall, which restricts the escape of undersized crabs. To enhance size selectivity without compromising capture efficiency, a modified trap was developed featuring a 2.5-inch wall mesh and a yellow-colored entrance. Fishing trials were conducted in September 2024 and October 2025 in Banten Bay using trash fish as bait. Data collected included the carapace width and weight of the crabs, as well as the total weight of bycatch. A descriptive analysis and scoring method were applied to evaluate trap effectiveness. The design parameters used in the scoring analysis are the percentage of crab weight, the percentage of bycatch weight, the percentage of crabs legal crab, the percentage of undersize crabs, and the average carapace width of the crab. The t-test equal variance was conducted to compare whether there was an effect of differences in trap designs on the weight of the crab obtained. Results indicated that the modified trap achieved a high effectiveness score (total = 18). The modified trap produced 82% of the total catch weight from target crabs and only 18% from bycatch. The use of a yellow entrance combined with a 2.5-inch wall mesh significantly improved the catch proportion of marketable-sized crabs while reducing bycatch biomass. Key words: entrance color, fishing efficiency, selectivity, trap wall